Photocatalytic oxidation of volatile organic compounds for indoor air applications - Bayless, Lynette Vera (Kansas State University, 2009)
Photocatalytic oxidation (PCO) is a promising and emerging technique in controlling indoor air contaminants, including volatile organic compounds (VOCs). It has broad air cleaning and deodorization applications in indoor environments ranging from residential and office buildings to healthcare and nursing facilities as well as spacecrafts, aircraft cabins and clean rooms in the agricultural and food industry. Numerous studies have been conducted to improve the effectiveness and performance of this technology. These include development of new configurations, energy-efficient catalysts and other parameters to control the process. However, only limited research has been conducted under realistic indoor environmental conditions. One of the most recent developments in photocatalysis is the synthesis of 2% C- and V-doped TiO[subscript]2, which is active under both dark and visible light conditions. However, like most research conducted in photocatalysis, the study on the reactivity of this catalyst has been performed only under laboratory conditions. This study investigated the possible application of the novel C and V co-doped TiO[subscript]2 in cleaning indoor air. Mathematical modeling and simulation techniques were employed to assess the potential use of some of the promising systems that utilize the catalyst (i.e., packed bed and thin films) as well as the effect of mass transfer limitations in the degradation of acetaldehyde, one of the VOCs that can be found in offices, residential buildings and other facilities.
Keywords: Indoor air cleaning; Modeling and simulation; Photocatalytic oxidation; Rate limitations; Visible light active; Volatile organic compounds; Engineering, Chemical (0542); Engineering, Environmental (0775); Environmental Sciences (0768)